Peranan Audit Sumber Daya Manusia Pada Pelatihan Dan Kompensasi Terhadap Kinerja Karyawan Dan Pengembangan Karir Sebagai Variable Intervening di Pt XYZ - Refi Tri Anika; Hwihanus Hwihanus (International Forum of Researchers and Lecturers, 2024)
This study aims to determine the role of human resource audits on training and compensation on employee performance and career development as an intervening variable at PT XYZ. The research uses descriptive quantitative method. The population in this study were employees of PT XYZ who were placed in outlets in Taman sub-district, Sidoarjo. The sampling technique in the study used Purposive Sampling Technique with the criteria of employees who deal directly with consumers totaling 35 people. Data obtained by filling out a questionnaire. The data was processed using the SmartPLS statistical tool and analyzed using the inner and outer models. The results of the study found that training and compensation have a positive and insignificant effect on employee performance and training has a positive and significant effect on career development.